Eigenvalues of antiadjacency matrix of Cayley graph of Z_n - Juan Daniel; Kiki Ariyanti Sugeng; Nora Hariadi (Indonesian Combinatorial Society (InaCombS), 2022)
In this paper, we give a relation between the eigenvalues of the antiadjacency matrix of Cay(Z_n, S) and the eigenvalues of the antiadjacency matrix of Cay(Z_n, (Z_n−0)−S), as well as the eigenvalues of the adjacency matrix of Cay(Z_n, S). Then, we give the characterization of connection set S where the eigenvalues of the antiadjacency matrix of Cay(Z_n, S) are all integers.